Pneumo-phono-articulatory coordination assessment in dysarthria cases: a cross-sectional study - Chappaz, Rebeca de Oliveira; Barreto, Simone dos Santos; Ortiz, Karin Zazo (São Paulo Medical Journal, 2018)
BACKGROUND: Pneumo-phono-articulatory coordination is often impaired in dysarthric patients. Because all speech is produced upon exhalation, adequate respiratory support and coordination are essential for communication. Nevertheless, studies investigating respiratory parameters for speech are scarce. The objectives of the present study were to analyze and compare the numbers of words and syllables (universal measurement) per exhalation among healthy and dysarthric speakers, in different speech tasks. DESIGN AND SETTING: A cross-sectional analytical study with a control group was conducted at the Department of Speech, Language and Hearing Sciences at UNIFESP. METHODS: The study sample consisted of 62 individuals: 31 dysarthric patients and 31 healthy individuals matched for sex, age and education level. All participants performed number counting and text reading tests in which the numbers of words and syllables per exhalation were recorded. All measurements obtained from the two groups were compared. RESULTS: Statistically significant differences between the dysarthric and healthy groups were found in the two tasks (counting of syllables and words per exhalation) (P < 0.001). In contrast, the perfomance of the dysarthric patients did not vary according to the task: reading and number counting in syllables/exhalation (P = 0.821) or words/exhalation (P = 0.785). CONCLUSIONS: The mean numbers of words and syllables per exhalation among dysarthric subjects did not vary according to the speech task used but they clearly showed differences between dysarthric patients and normal healthy subjects. The study also made it possible to obtain preliminary data on the average numbers of words and syllables per expiration produced by healthy individuals during their speech production.